Effect of thermal pretreatment on chemical composition and biogas production from kitchen waste - Wordofa, Gossa (2014)
Biogas has been well known with its wide range of benefits in terms of greenhouse reduction,energy security, creating jobs and generating revenue. However, biological conversion of several biogas feedstocks to biogas under anaerobic digestion has proven inefficient due to low conversion efficiency. Pretreatment of certain type of biomass has been known to improve the biodegradability and methane yield of the pretreated biomass. In this study, the effect of thermal pretreatments viz., pressure-cooking with steam (PC1), pressure-cooking with water (PC2), steam pretreatment in steamer and hydrothermal pretreatments on chemical composition and methane potential of kitchen waste was investigated. Grab samples of kitchen waste were collected from Yliotö restaurant located on the Ylistönrinne campus of the University of Jyväskylä. Methane production from untreated and pretreated kitchen waste was determined in batch experiments at 35 °C and 55 °C.